Critical Review of Osloobia Albayanol Arabi Men Ofogh alghavaedolmeyaria Elaafagh E-nnaselebdaee - Moosa Arabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
After emergence of Islam, by its miraculous style of expression, holy Quran attracted Muslims’ attention to rhetoric and aesthetics; this literati and critics fascination to miraculous style led them to move through regularization of rhetoric and aesthetics; in the meantime, by the advances in criticism and emergence of literary movements, there were some reactions to traditional approaches to rhetoric, showing themselves in names such as Osloobie.With regard to the new stylistics, numerous compilations were written by the critics, and in this study, the aim is to analyze one of this works, that is Osloobia albayanol arabi men ofogh alghavaedolmeyaria Elaafagh E-nnaselebdaee by Rahman Gharkan.This work was analyzed based on the content analysis method and the most significant results are mentioned in the part about pros and cons of the book. The most significant pros and cons include, a detailed boundary between old rhetoric and new rhetoric, which, by a practical part called “gheraatvanass” has led the author to succeed more in comparison to similar works The appropriateness of the title to the content is obvious in all chapters and two keywords “elghavaedolmeyariaelaafagh e-nnaselebdaee” has been analyzed in all chapters using evidences and references. A civilized and dynamic look to language as a live body in which rhetoric issues as well as modern literature have been used with a new perspective; presenting comprehensive analysis by the author at the end of each chapter which leads the reader to have a clear understanding about Osloobiaalbayanolarabi, logical discipline and order of book discussions are among the strengths of the book. Some editing and writing mistakes, compaction of book discussion and lack of exercises and tests, not having concordances, verses and poems, not evaluating and criticizing the view of western scholars are among the weak points.